PENGARUH PENDAPATAN PERKAPITA DAN PENDAPATAN ASLI DAERAH (PAD) TAHUN SEBELUMNYA TERHADAP REALISASI PENDAPATAN ASLI DAERAH (PAD) KABUPATEN KUTAI BARAT - Lidia Elly (Jurnal Ekonomi Pembangunan, 2013)
The objectives of this study were: 1) to analyze and determine the effect of per capita income and revenue (PAD) in the previous year on the realization of revenue (PAD) in West Kutai Regency 2) to analyze and determine which one is the most elastic to the realization of revenue (PAD) in West Kutai Regency between per capita income and revenue (PAD) in the previous year; and 3) to analyze and determine the timing of realization of revenue (PAD) in West Kutai Regency. To determine the extent of the influence of per capita income and revenue (PAD) in the previous year on revenue (PAD) in West Kutai Regency, the researcher use multiple liner regression models from Cobb-Douglas production function model to obtain data about per capita income and revenue (PAD) in the previous year. The result show that per capita incme affects directy and significantly towards the realization of revenue (PAD) in West Kutai Regency; and per capitaincome has an elastic and great influence on the realization of revenue (PAD) in West Kutai Regency